tìm x : 13/6 : x = 2 - 2/5
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
X + 5/9 = 4/3
X = 4/3 - 5/9
X = 7/9
X - 4/9 = 1/2
X = 1/2 + 4/9
X = 17/18
6/13 + X = 7/6
X = 7/6 - 6/13
X = 55/78
13/5 - X = 5/6
X = 13/5 - 5/6
X= 53/30
X + 5/9 = 4/3
x = 4/3 - 5/9
x = 7/9
X - 4/9 = 1/2
x = 1/2 + 4/9
x = 17/18
6/13 + X = 7/6
x = 7/6 - 6/13
x - 55/78
13/5 - X = 5/6
x = 13/5 - 5/6
x = 53/30
1: x=3/4-1/2=3/4-2/4=1/4
2: x-1/5=2/11
=>x=2/11+1/5=21/55
3: x-5/6=16/42-8/56
=>x-5/6=8/21-4/28=5/21
=>x=5/21+5/6=15/14
4: x/5=5/6-19/30
=>x/5=25/30-19/30=6/30=1/5
=>x=1
5: =>|x|=1/3+1/4=7/12
=>x=7/12 hoặc x=-7/12
6: x=-1/2+3/4
=>x=3/4-1/2=1/4
11: x-(-6/12)=9/48
=>x+1/2=3/16
=>x=3/16-1/2=-5/16
1)x= 1/4
2)x= 2/11+ 1/5
x= 21/55
3)x - 5/6 = 5/21
x = 5/21+5/6
x = 15/14
4)x/5 = 5/6 + -19/30
x:5 = 1/5
x = 1/5.5
x = 1
5) |x| - 1/4 = 6/18
|x| = 6/18 - 1/4
|x| =7/12
⇒x= 7/12 hoặc -7/12
6)x = -1/2 +3/4
x= 1/4
7) x/15 = 3/5 + -2/3
x:15 = -1/15
x = -1/15. 15
x = -1
8)11/8 + 13/6 = 85/x
85/24 = 85/x
⇒ x = 24
9) x - 7/8 = 13/12
x = 13/12 + 7/8
x = 47/24
10)x - -6/15 = 4/27
x = 4/27 + (-6/15)
x = -34/135
11) -(-6/12)+x = 9/48
x= 9/48 - 6/12
x = -5/16
12) x - 4/6 = 5/25 + -7/15
x -4/6 = -4/15
x = -4/15 + 4/6
x = 2/5
a) \(x:\dfrac{6}{13}=\dfrac{13}{7}\\ \Rightarrow x=\dfrac{13}{7}.\dfrac{6}{13}\\ \Rightarrow x=\dfrac{6}{7}\)
b) \(\dfrac{4}{7}.x-\dfrac{2}{3}=\dfrac{1}{5}\\ \Rightarrow\dfrac{4}{7}.x=\dfrac{13}{15}\\ \Rightarrow x=\dfrac{91}{60}\)
c) \(\left(\dfrac{3}{10}-x\right):\dfrac{2}{5}=\dfrac{3}{5}\\ \Rightarrow\dfrac{3}{10}-x=\dfrac{6}{25}\\ \Rightarrow x=\dfrac{3}{50}\)
d) \(\dfrac{2}{3}x-\dfrac{7}{6}=\dfrac{5}{2}\\ \Rightarrow\dfrac{2}{3}x=\dfrac{11}{3}\\ \Rightarrow x=\dfrac{11}{2}\)
a)
`x/(-8)=5/4`
`=>x*4=5*(-8)`
`=>4x=-40`
`=>x=-40:4`
`=>x=-10`
b)
`(-13)/x=(-65)/10`
`=>(-13)/x=(-13)/2`
`=>x=2`
c)
`(-6)/5=(-12)/x`
`<=>(-12)/10=(-12)/x`
`<=>x=10`
d)
`(x-2)/2=8/(x-2)`
`=>(x-2)(x-2)=8*2`
`=>(x-2)^2=16`
`=>x-2=4` hoặc`x-2=-4`
`=>x=4+2` hoặc `x=-4+2`
`=>x=6` hoặc `x=-2`
`x/(-8) = 5/4`
`=> 4x=5.(-8)`
`=>4x=-40`
`=>x=-40:4`
`=>x=-10`
__
`-13/x =-65/10`
`=> -65x=-130`
`=>x=-130:(-65)`
`=>x= 2`
__
`-6/5 =-12/x`
`=> -6x=-12.5`
`=> -6x= -60`
`=>x=-60:(-6)`
`=>x=10`
__
`(x-2)/2 = 8/(x-2)`
`=>(x-2)^2=2.8`
`=>(x-2)^2=16`
`=> (x-2)^2=+-4^2`
\(\Rightarrow\left[{}\begin{matrix}x-2=4\\x-2=-4\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=6\\x=-2\end{matrix}\right.\)
\(\frac{1}{3}-\left(\frac{2}{3}-x+\frac{5}{4}\right)=\frac{7}{12}-\left(\frac{5}{2}-\frac{13}{6}\right)\)
\(\frac{1}{3}-\left(\frac{2}{3}-x+\frac{5}{4}\right)=\frac{7}{12}-\frac{1}{3}\)
\(\frac{1}{3}-\left(\frac{2}{3}-x+\frac{5}{4}\right)=\frac{1}{4}\)
\(\frac{2}{3}-x+\frac{5}{4}=\frac{1}{3}-\frac{1}{4}\)
\(\frac{2}{3}-x+\frac{5}{4}=\frac{1}{12}\)
\(\frac{2}{3}-x=\frac{1}{12}-\frac{5}{4}\)
\(\frac{2}{3}-x=-\frac{7}{6}\)
\(x=\frac{2}{3}-\left(-\frac{7}{6}\right)\)
\(x=\frac{2}{3}+\frac{7}{6}\)
\(x=\frac{11}{6}\)
\(\frac{7}{5}x+\frac{13}{2}+\frac{6}{3}x=\frac{1}{15}x+\frac{17}{2}\)
=\(\frac{7}{5}x+\frac{6}{3}x-\frac{1}{15}x=\frac{17}{2}-\frac{13}{2}\)
\(\frac{10}{3}x=2\)
x=\(\frac{3}{5}\)
\(\frac{7}{5}.x+\frac{13}{2}+\frac{6}{3}.x=\frac{1}{15}.x+\frac{17}{2}\)
\(\left(\frac{7}{5}+2\right).x+\frac{13}{2}=\frac{1}{15}.x+\frac{17}{2}\)
\(\frac{17}{5}.x+\frac{13}{2}=\frac{1}{15}.x+\frac{17}{2}\)
\(\frac{17}{5}.x-\frac{1}{15}.x=\frac{17}{2}-\frac{13}{2}\)
\(\left(\frac{17}{5}-\frac{1}{15}\right)x=2\)
\(\frac{10}{3}.x=2\)
\(x=2:\frac{10}{3}\)
\(x=\frac{3}{5}\)
a x là 13/13
b, 2/3 * x - 1/2 = 5/6
2/3 * x = 5/6 + 1/2
2/3 * x = 8/6
x = 8/6 : 2/3
x = 2
\(\dfrac{13}{6}:x=2-\dfrac{2}{5}\)
\(\dfrac{13}{6}:x=\dfrac{10}{5}-\dfrac{2}{5}\)
\(\dfrac{13}{6}:x=\dfrac{8}{5}\)
\(x=\dfrac{13}{6}:\dfrac{8}{5}\)
\(x=\dfrac{13}{6}x\dfrac{5}{8}\)
\(x=\dfrac{65}{48}\)